The complete mitochondrial genome of the Neophocaena asiaeorientails sunamrei (Phocaenidae: Neophocaena). (4th March 2017) - Cheng, Yaxin; Liu, Dong; Tang, Wenqiao
Abstract: The complete sequence of the mitochondrial DNA (mtDNA) of the East Asian finless porpoise ( Neophocaena asiaeorientails sunamrei ) has been completed and annotated in this study. The circular genome is 16 385 bp in length, consisting of 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and 2 non-coding areas. Ten protein-coding genes use ATG as the initiation codon, except that ND2 started with ATT, and ND3 and ND5 started with ATA. Canonical TAA and TAG termination codons are found in seven protein-coding genes, the remaining four ( ND4, ND2, ND3, and COIII ) have incomplete termination codons (T or TA), in addition, the COI ends with AGG, and the Cyt b ends with AGA. On the neighbor-joining phylogenetic tree, these results show that the relationship of Phocoenidae is closer with Delphinidae.